TBX6 missense variants expand the mutational spectrum in a non-Mendelian inheritance disease. - Chen, Weisheng; Lin, Jiachen; Wang, Lianlei; Li, Xiaoxin; Zhao, Sen; Liu, Jiaqi; Akdemir, Zeynep C; Zhao, Yanxue; Du, Renqian; Ye, Yongyu; Song, Xiaofei; Zhang, Yuanqiang; et al. (Hum Mutat, 2020)
Congenital scoliosis (CS) is a birth defect with variable clinical and anatomical manifestations due to spinal malformation. The genetic etiology underlying about 10% of CS cases in the Chinese population is compound inheritance by which the gene dosage is reduced below that of haploinsufficiency. In this genetic model, the trait manifests as a result of the combined effect of a rare variant and common pathogenic variant allele at a locus. From exome sequencing (ES) data of 523 patients in Asia and two patients in Texas, we identified six TBX6 gene-disruptive variants from 11 unrelated CS patients via ES and in vitro functional testing. The in trans mild hypomorphic allele was identified in 10 of the 11 subjects; as anticipated these 10 shared a similar spinal deformity of hemivertebrae. The remaining case has a homozygous variant in TBX6 (c.418C>T) and presents a more severe spinal deformity phenotype. We found decreased transcriptional activity and abnormal cellular localization as the molecular mechanisms for TBX6 missense loss-of-function alleles. Expanding the mutational spectrum of TBX6 pathogenic alleles enabled an increased molecular diagnostic detection rate, provided further evidence for the gene dosage-dependent genetic model underlying CS, and refined clinical classification.
Keywords: Alleles; Cell Line; Female; Gene Expression; Genes, Reporter; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inheritance Patterns; Male; Models, Molecular; Molecular Diagnostic Techniques; Mutation, Missense; Phenotype; Protein Conformation; Radiography; Sequence Analysis, DNA; Spine; Structure-Activity Relationship; T-Box Domain Proteins; Whole Exome Sequencing

TBX6 compound inheritance leads to congenital vertebral malformations in humans and mice. - Yang, Nan; Wu, Nan; Zhang, Ling; Zhao, Yanxue; Liu, Jiaqi; Liang, Xiangyu; Ren, Xiaojun; Li, Weiyu; Chen, Weisheng; Dong, Shuangshuang; Zhao, Sen; Lin, Jiachen; et al. (Hum Mol Genet, 2019)
Congenital vertebral malformations (CVMs) are associated with human TBX6 compound inheritance that combines a rare null allele and a common hypomorphic allele at the TBX6 locus. Our previous in vitro evidence suggested that this compound inheritance resulted in a TBX6 gene dosage of less than haploinsufficiency (i.e. <50%) as a potential mechanism of TBX6-associated CVMs. To further investigate this pathogenetic model, we ascertained and collected 108 Chinese CVM cases and found that 10 (9.3%) of them carried TBX6 null mutations in combination with common hypomorphic variants at the second TBX6 allele. For in vivo functional verification and genetic analysis of TBX6 compound inheritance, we generated both null and hypomorphic mutations in mouse Tbx6 using the CRISPR-Cas9 method. These Tbx6 mutants are not identical to the patient variants at the DNA sequence level, but instead functionally mimic disease-associated TBX6 variants. Intriguingly, as anticipated by the compound inheritance model, a high penetrance of CVM phenotype was only observed in the mice with combined null and hypomorphic alleles of Tbx6. These findings are consistent with our experimental observations in humans and supported the dosage effect of TBX6 in CVM etiology. In conclusion, our findings in the newly collected human CVM subjects and Tbx6 mouse models consistently support the contention that TBX6 compound inheritance causes CVMs, potentially via a gene dosage-dependent mechanism. Furthermore, mouse Tbx6 mutants mimicking human CVM-associated variants will be useful models for further mechanistic investigations of CVM pathogenesis in the cases associated with TBX6.
Keywords: Adolescent; Alleles; Animals; Child; Child, Preschool; Congenital Abnormalities; CRISPR-Cas Systems; Disease Models, Animal; Female; Haploinsufficiency; Humans; Infant; Male; Mice; Mutation; Phenotype; Scoliosis; Spine; T-Box Domain Proteins

De Novo Mutations in SON Disrupt RNA Splicing of Genes Essential for Brain Development and Metabolism, Causing an Intellectual-Disability Syndrome. - Kim, Jung-Hyun; Shinde, Deepali N; Reijnders, Margot R F; Hauser, Natalie S; Belmonte, Rebecca L; Wilson, Gregory R; Bosch, Daniëlle G M; Bubulya, Paula A; Shashi, Vandana; Petrovski, Slavé; Stone, Joshua K; Park, Eun Young; et al. (Am J Hum Genet, 2016)
The overall understanding of the molecular etiologies of intellectual disability (ID) and developmental delay (DD) is increasing as next-generation sequencing technologies identify genetic variants in individuals with such disorders. However, detailed analyses conclusively confirming these variants, as well as the underlying molecular mechanisms explaining the diseases, are often lacking. Here, we report on an ID syndrome caused by de novo heterozygous loss-of-function (LoF) mutations in SON. The syndrome is characterized by ID and/or DD, malformations of the cerebral cortex, epilepsy, vision problems, musculoskeletal abnormalities, and congenital malformations. Knockdown of son in zebrafish resulted in severe malformation of the spine, brain, and eyes. Importantly, analyses of RNA from affected individuals revealed that genes critical for neuronal migration and cortex organization (TUBG1, FLNA, PNKP, WDR62, PSMD3, and HDAC6) and metabolism (PCK2, PFKL, IDH2, ACY1, and ADA) are significantly downregulated because of the accumulation of mis-spliced transcripts resulting from erroneous SON-mediated RNA splicing. Our data highlight SON as a master regulator governing neurodevelopment and demonstrate the importance of SON-mediated RNA splicing in human development.
Keywords: Animals; Brain; Developmental Disabilities; DNA-Binding Proteins; Eye Abnormalities; Female; Genes, Essential; Haploinsufficiency; Head; Heterozygote; Humans; Intellectual Disability; Male; Metabolic Diseases; Minor Histocompatibility Antigens; Mutation; Pedigree; RNA Splicing; RNA, Messenger; Spine; Syndrome; Zebrafish

An anadysplasia-like, spontaneously remitting spondylometaphyseal dysplasia secondary to lamin B receptor (LBR) gene mutations: further definition of the phenotypic heterogeneity of LBR-bone dysplasias. - Sobreira, Nara; Modaff, Peggy; Steel, Gary; You, Jing; Nanda, Sonia; Hoover-Fong, Julie; Valle, David; Pauli, Richard M (Am J Med Genet A, 2015)
We describe a boy who has an anadysplasia-like spondylometaphyseal dysplasia. By whole exome sequencing he was shown to have compound heterozygous mutations of LBR that codes for the lamin B receptor. He shares many similarities with a case previously described, but in whom the early natural history could not be established [Borovik et al., 2013]. Thus, in addition to Greenberg dysplasia (a perinatal lethal disorder), homozygosity or compound heterozygosity of mutations in LBR can result in a mild, spontaneously regressing bone dysplasia.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Humans; Infant; Infant, Newborn; Male; Mutation; Osteochondrodysplasias; Phenotype; Pregnancy; Radiography; Receptors, Cytoplasmic and Nuclear; Spine

Rare variants in the notch signaling pathway describe a novel type of autosomal recessive Klippel-Feil syndrome. - Karaca, Ender; Yuregir, Ozge O; Bozdogan, Sevcan T; Aslan, Huseyin; Pehlivan, Davut; Jhangiani, Shalini N; Akdemir, Zeynep C; Gambin, Tomasz; Bayram, Yavuz; Atik, Mehmed M; Erdin, Serkan; Muzny, Donna; et al. (Am J Med Genet A, 2015)
Klippel-Feil syndrome is a rare disorder represented by a subgroup of segmentation defects of the vertebrae and characterized by fusion of the cervical vertebrae, low posterior hairline, and short neck with limited motion. Both autosomal dominant and recessive inheritance patterns were reported in families with Klippel-Feil. Mutated genes for both dominant (GDF6 and GDF3) and recessive (MEOX1) forms of Klippel-Feil syndrome have been shown to be involved in somite development via transcription regulation and signaling pathways. Heterotaxy arises from defects in proteins that function in the development of left-right asymmetry of the developing embryo. We describe a consanguineous family with a male proband who presents with classical Klippel-Feil syndrome together with heterotaxy (situs inversus totalis). The present patient also had Sprengel's deformity, deformity of the sternum, and a solitary kidney. Using exome sequencing, we identified a homozygous frameshift mutation (c.299delT; p.L100fs) in RIPPLY2, a gene shown to play a crucial role in somitogenesis and participate in the Notch signaling pathway via negatively regulating Tbx6. Our data confirm RIPPLY2 as a novel gene for autosomal recessive Klippel-Feil syndrome, and in addition-from a mechanistic standpoint-suggest the possibility that mutations in RIPPLY2 could also lead to heterotaxy. © 2015 Wiley Periodicals, Inc.
Keywords: Adolescent; Base Sequence; Female; Humans; Klippel-Feil Syndrome; Male; Molecular Sequence Data; Mutation; Pedigree; Radiography; Receptors, Notch; Signal Transduction; Spine

TBX6 null variants and a common hypomorphic allele in congenital scoliosis. - Wu, N; Ming, X; Xiao, J; Wu, Z; Chen, X; Shinawi, M; Shen, Y; Yu, G; Liu, J; Xie, H; Gucev, Z S; Liu, S; et al. (N Engl J Med, 2015)
BACKGROUND: Congenital scoliosis is a common type of vertebral malformation. Genetic susceptibility has been implicated in congenital scoliosis. METHODS: We evaluated 161 Han Chinese persons with sporadic congenital scoliosis, 166 Han Chinese controls, and 2 pedigrees, family members of which had a 16p11.2 deletion, using comparative genomic hybridization, quantitative polymerase-chain-reaction analysis, and DNA sequencing. We carried out tests of replication using an additional series of 76 Han Chinese persons with congenital scoliosis and a multicenter series of 42 persons with 16p11.2 deletions. RESULTS: We identified a total of 17 heterozygous TBX6 null mutations in the 161 persons with sporadic congenital scoliosis (11%); we did not observe any null mutations in TBX6 in 166 controls (P<3.8×10(-6)). These null alleles include copy-number variants (12 instances of a 16p11.2 deletion affecting TBX6) and single-nucleotide variants (1 nonsense and 4 frame-shift mutations). However, the discordant intrafamilial phenotypes of 16p11.2 deletion carriers suggest that heterozygous TBX6 null mutation is insufficient to cause congenital scoliosis. We went on to identify a common TBX6 haplotype as the second risk allele in all 17 carriers of TBX6 null mutations (P<1.1×10(-6)). Replication studies involving additional persons with congenital scoliosis who carried a deletion affecting TBX6 confirmed this compound inheritance model. In vitro functional assays suggested that the risk haplotype is a hypomorphic allele. Hemivertebrae are characteristic of TBX6-associated congenital scoliosis. CONCLUSIONS: Compound inheritance of a rare null mutation and a hypomorphic allele of TBX6 accounted for up to 11% of congenital scoliosis cases in the series that we analyzed. (Funded by the National Basic Research Program of China and others.).
Keywords: Adolescent; Asian Continental Ancestry Group; Child; Child, Preschool; Chromosomes, Human, Pair 16; DNA Copy Number Variations; Female; Genetic Predisposition to Disease; Genotype; Humans; Male; Mutation; Pedigree; Phenotype; Radiography; Scoliosis; Sequence Deletion; Spine; T-Box Domain Proteins